consider

f(a,n) = f(a,n-1)^2 - f(a,n-1)

g(b,n) = g(b,n-1)^2

lim n = oo f(k(b),n) = g(b,n)

notice k(1) =/= 2 because of the upper fixpoints of f (fixpoint x^2 - x) and g (fixpoint x^2) but approaches it.

does k(x+1) have a positive radius when expanded at x = 0 ?

regards

tommy1729

f(a,n) = f(a,n-1)^2 - f(a,n-1)

g(b,n) = g(b,n-1)^2

lim n = oo f(k(b),n) = g(b,n)

notice k(1) =/= 2 because of the upper fixpoints of f (fixpoint x^2 - x) and g (fixpoint x^2) but approaches it.

does k(x+1) have a positive radius when expanded at x = 0 ?

regards

tommy1729